Morpho-anatomical characterization of stems of Cyperus articulatus L. and C. prolixus H.B.K. (Cyperaceae) - dos Santos, Pedro Paulo; Potiguara, Raimunda Conceição de Vilhena; Lins, Alba Lúcia Ferreira de Almeida; Macedo, Eunice Gonçalves (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
Cyperus articulatus and C. prolixus are known as priprioca and pripriocão, respectively. In these species, there are disagreements on the nomenclature of the stems, which receive different names, causing difficulties in the taxa identification. The objective of this paper is the characterization of the C. articulatus and C. prolixus stems, through the description of morphology, morphometric data, function, anatomy and histochemistry. Samples were collected in a growth experiment in the Universidade Federal Rural da Amazônia (UFRA), Belém municipality, and the plants are originally from Acará municipality, Pará state. The material was described, measured, fixed in FAA70, and studied following usual anatomy techniques and histochemical tests. The stems are of two types rhizome and corm. They are subterranean, plagiotropic and surrounded by cataphylls. The rhizome is monopodial and cylindrical, while the corm is swollen. These two stems are perennial, the corm has propagation function and the rhizome has expansion function. Regarding anatomy, these stems have active primary thickening meristem, but only corms have secondary thickening meristem activity and produce adventitious roots.
Keywords: Monocotyledoneae; Rhizome; Corm